The Use of Augmented Reality for the Management of Equipment Ageing with a Virtual Sensor - Giuseppa Ancione; Rebecca Saitta; Paolo Bragatto; Giacomo Fiumara; Maria Francesca Milazzo (Applied Sciences, 2023)
Much of the equipment that is used in the chemical and process industry and for handling or treating hazardous substances is subject to deterioration. To manage the risk of major accidents due to this deterioration, the current legislation requires periodic controls that must be carried out to verify the health conditions (ageing). To support the inspectors performing this task, a virtual sensor has been designed and developed. It is a system composed of hardware and software that uses mathematical models and augmented reality to assist in on-field inspections for monitoring and predicting equipment ageing. Currently, there are no AR devices to perform inspections aimed at verifying the integrity of equipment. The virtual sensor collects ageing-related information and returns the corrosion rate, the probability of the critical pit, the corrosion evolution through iso-contour corrosion maps, and the RUL; finally, it allows visualising the equipment condition through augmented reality, (e.g., by means of thickness maps and tables that overlay the equipment). The aim of this paper is to present the graphical interface of the software application, which has been improved to minimise errors due to human–machine interaction. A large diesel storage tank has been used to show how the virtual sensor works.